Monitoring the agri-food system in Myanmar: Maize farmers – Monsoon season phone surveys - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand the effects of recent economic and political disruptions on Myanmar’s maize farmers during the monsoon season, we conducted two telephone surveys with 1,178 farmers in July and September 2021. Key Findings There were widespread disruptions throughout the 2021 monsoon season: 11 percent of respondents were displaced by violence in July, and most farmers had had enforced transportation restrictions in their village tracts (58 percent) and their townships (84 percent). Seventy percent of farmers expect these restrictions to affect their monsoon marketing. Two-thirds of respondents received farm credit for inputs in the 2021 monsoon season, an increase of 3 percentage points relative to 2020, and average credit values increased slightly. Most credit was provided by traders (27 percent receiving), which may be unique to maize production as there are broader credit declines in other parts of the country and maize prices have increased in 2021. Additionally, exports to Thailand have been robust. High fertilizer prices will likely lead to a decline in application rates as 63 percent of farmers reported reduced input use, which will negatively affect yields. Median maize farm sizes fell by one acre in 2021 relative to 2020, though average maize acreages were stable. Pest incidence rates (72 percent reporting problems), especially for fall armyworm (45 percent), were high in July, posing another threat to production. There was a decline in access to formal extension services, particularly for information provided by input companies and government extension agents. Farmers increasingly turned to neighbors for agricultural advice.